COVID-19 Transmission due to Mass Mobility Before and After the Largest Festival in Bangladesh: An Epidemiologic Study - Farah Naz Rahman Msc; A. K. M. Fazlur Rahman PhD; Anthony Obinna Iwuagwu Msc; Koustuv Dalal PhD (SAGE Publishing, 2021)
Festivals traditionally result in mass public mobility from large cities to rural or semi-urban areas in low- and middle-Income Countries (LMIC), which are inadequately prepared for tackling the consequences of the COVID-19 pandemic. This study aimed to explore the trend of COVID-19 infection in a peripheral region of Bangladesh during one of the largest festivals to develop an evidence-based hypothesis for its influence on the transmission rate of COVID-19. This study conducted a quantitative analysis of secondary data on COVID-19 collected from the Directorate General of Health Services Bangladesh (DGHS) and divisional director's office in the Mymensingh division. To explore the influence of one of the biggest festivals (Eid-ul-Adha) on the trend of COVID-19 infection, we analyzed data from a week before the festival to 2 weeks following the festival. The infection rate (positive cases per million of the population) and the test positivity rate (positive cases among the total number of conducted diagnostic tests) of each day during this period were calculated both for the Mymensingh region and national level. Both the test positivity rate (TPR) and infection rates in the Mymensingh region demonstrated an increasing trend. The mean test positivity rate of the Mymensingh region on the week before the festival was 9.5%. It increased to a mean test positivity rate of 13% in the following week and further rose to a rate of 17% in the next week. The infection rate of Mymensingh also increased more than 2 folds from the day of the festival (2.0-5.3 cases per million) within the next 2 weeks. The TPR and infection rate on the national level remained similar throughout the study period. Mass mobility during Eid-ul-Adha influences the increased transmission of COVID-19 among the peripheral regions of Bangladesh from the central capital city Dhaka. The findings will help policymakers plan and implement travel restrictions during festivals during the pandemic in LMICs.